The Effects of Increasing the Full Retirement Age from 66 to 67 on the Retirement Decision at the Early Retirement Age of 62 - Son, Chong-Hwan (Archives of Business Research, 2024)
In the United States, the full retirement age increases in two-month increments each year until reaching 67 years of age in 2027 for individuals born from 1955 to 1960. The increase in the full retirement age is equivalent to a decline in the Social Security benefits for all new retirees. If the full retirement age is increased from 66 to 67 while the early retirement age remains at 62, then the monthly benefit reduction at age 62 would increase from 25% to 30%. Despite the reduction in Social Security benefits, a significant portion of newly retired workers claim their Social Security benefits as soon as they turn 62, which is the earliest age to claim the benefit. The Social Security Administration predicts that the reduction in Social Security benefits can encourage workers to delay their retirement and that the reduction can restore some financial balance to the Social Security system. Therefore, studying the effects of increasing the full retirement age from 66 to 67 on the retirement decision at 62 is essential for planning future social security reforms. This study conducts a Two-Stage Least Squares (2SLS) regression, using cross-sectional and time series data from the Behavioral Risk Factor Surveillance System (BRFSS) from 2016 to 2021. The empirical results show that the probability of retirement for individuals at age 62 decreased from 2016 to 2021, indicating a trend of delaying retirement as their full retirement age rises. During the same period, the likelihood of men reporting being retired decreases by 35.56%, while for women, it drops by 16.79%. It implies that if male and female workers choose to exit the workforce solely based on the Social Security benefits, the increase in full retirement age appears to have a more significant impact on delaying retirement decisions for male workers than for female workers.